2022
DOI: 10.1089/heq.2022.0033
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequities in Vaccine Hesitancy Among Native Hawaiians and Pacific Islanders

Abstract: Purpose: COVID-19 vaccine hesitancy exists in communities of color who are disproportionately impacted by COVID-19. In many states, Native Hawaiians and Pacific Islanders (NHs/PIs) experience the highest rates of COVID-19 confirmed cases and mortality among U.S. ethnic/racial groups. National trends regarding vaccine hesitancy among NHs/PIs are currently lacking. Methods: Data were derived from the Asian American and NH/PI COVID-19 Needs Assessment Project, a national s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…The present study elucidated interesting trends across sexual orientation for the perceived likelihood of receiving the COVID-19 vaccine. Our multivariate logistic regression analysis yielded similar findings to previous literature as individuals who reported lower income (heterosexual respondents) and education levels (heterosexual and sexual minority respondents) were less likely to report being likely to receive the COVID-19 vaccine [ 29 , 30 , 31 , 32 , 33 ]. This illustrates an important area of concern and intervention for vaccine education and promotion, given individuals of lower socioeconomic status have the highest risk for poor respiratory health [ 34 ].…”
Section: Discussionsupporting
confidence: 84%
“…The present study elucidated interesting trends across sexual orientation for the perceived likelihood of receiving the COVID-19 vaccine. Our multivariate logistic regression analysis yielded similar findings to previous literature as individuals who reported lower income (heterosexual respondents) and education levels (heterosexual and sexual minority respondents) were less likely to report being likely to receive the COVID-19 vaccine [ 29 , 30 , 31 , 32 , 33 ]. This illustrates an important area of concern and intervention for vaccine education and promotion, given individuals of lower socioeconomic status have the highest risk for poor respiratory health [ 34 ].…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, other Pacific Islanders, who make up only 4% of the population, comprised 25% of the COVID-19 cases in this same period and 14% of deaths overall [ 5 ]. Similarly, national research has shown that vaccine hesitance varies widely by ethnicity, from 56.3% among Tongans in the USA to 23.6% among Native Hawaiians [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…24 Samoa et al used data from the AA and NH/PI COVID-19 Needs Assessment Project and found that vaccine hesitancy ranged from 23% among NH/PIs to 57% among Tongans, with consistent associations between socioeconomic status and vaccine hesitancy among Native Hawaiians, Samoans, and Multi-ethnic NH/PIs. 25 …”
mentioning
confidence: 99%